The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.1461-0248.2004.00677.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental warming causes large and rapid species loss, dampened by simulated grazing, on the Tibetan Plateau

Abstract: We investigated the independent and combined effects of experimental warming and grazing on plant species diversity on the north-eastern Tibetan Plateau, a region highly vulnerable to ongoing climate and land use changes. Experimental warming caused a 26-36% decrease in species richness, a response that was generally dampened by experimental grazing. Higher species losses occurred at the drier sites where N was less available. Moreover, we observed an indirect effect of climate change on species richness as me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
377
4
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 488 publications
(406 citation statements)
references
References 45 publications
20
377
4
5
Order By: Relevance
“…Zhang (2011) also stated that wetlands in the Damqu River Basin located in the source region of the Yangtze River have experienced complex intercategory transformations, although the total wetland area has remained essentially unchanged throughout 1998 and 2007. Through experimental warming, Klein et al (2004) found that warming caused large and rapid species loss. Warming may change species geographic ranges as being reported in temperate regions (Iverson and Prasad, 1998;Lenoir et al, 2008 andMoritz et al, 2008) and threaten biodiversity within the TRSR.…”
Section: Response Of Water Resources On the Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…Zhang (2011) also stated that wetlands in the Damqu River Basin located in the source region of the Yangtze River have experienced complex intercategory transformations, although the total wetland area has remained essentially unchanged throughout 1998 and 2007. Through experimental warming, Klein et al (2004) found that warming caused large and rapid species loss. Warming may change species geographic ranges as being reported in temperate regions (Iverson and Prasad, 1998;Lenoir et al, 2008 andMoritz et al, 2008) and threaten biodiversity within the TRSR.…”
Section: Response Of Water Resources On the Climate Changementioning
confidence: 99%
“…Some examples are the expansion and increasing number of glacial lakes, a trend in decreasing snow coverage, shorter lake and river ice freezing periods, glacial ablation, and increasing surface instability of permafrost as well as its declining area (IPCC, 2007). Climate change has also caused ecosystem degradation (Lian and Shu, 2009), loss in biodiversity that only time can recover (Klein et al, 2004, Lenoir et al, 2008, and observable changes to plant species (Lenoir et al, 2008;Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This was surprising, as soil transplant or maize cropping alone significantly increased microbial diversity ( Supplementary Figures S1 and S4A). To explore this, we calculated the interactive effect of cropping and transplant on microbial diversity, using an established method (Klein et al, 2004). The results showed that the interactive effect of cropping and transplant was negative (Supplementary Figure S5).…”
Section: Vegetation Overrides Soil Transplant Effects On Microbial Comentioning
confidence: 99%
“…The Tibetan plateau, one of the most extensive alpine regions in the world, is thought to be particularly sensitive to global climate change (Klein et al, 2004). Moreover, as one of the largest pastoralist areas globally, the Tibetan plateau has been subjected…”
Section: Introductionmentioning
confidence: 99%
“…Klein et al (2004) reported that experimental warming caused a rapid decrease in species richness on the eastern Tibetan plateau, an effect that was dampened by simulated grazing. Similar findings have been reported elsewhere (Post and Pedersen, 2008).…”
Section: Introductionmentioning
confidence: 99%